Reducing the risks from occupational noise (Luxembourg, 2005)
"Every day, millions of employees in Europe are exposed to noise at work and all the risks this can entail. While noise is most obviously a problem in industries such as metal manufacturing and construction, it can also be an issue in a wide range of other workplaces, from airports to farms, call centres to concert halls. The European Agency for Safety and Health at Work has looked at how the European directive structure and the standards that complement it work to ensure that risks to workers from noise are addressed to reduce the high personal, social, and economic cost of ill health, stress and accidents arising from noise exposure. " (Publisher's presentation)